Students’ Perception on the Use of Nearpod in Learning English at the Seventh Grade Students of SMP Petra Berkat Denpasar - I Ketut Suar Adnyana; I Komang Dedik Susila; Ni Putu Ari Widiyani (Widya Accarya, 2023)
This study aims at determining students’ perceptions of the use of Nearpod for learning English in VII Grade students of SMP Petra Berkat Denpasar. This study implements a quantitative approach with observation and survey (non-test) techniques. The population of this study is the VII Grade of SMP Petra Berkat Denpasar in academic year 2021/2022. The findings show that the use of Nearpod media during online learning during the Covid-19 pandemic considers that Nearpod is in convenience criteria and very good criteria for Nearpod performance and student learning activities with Nearpod. This study shows positive perceptions of students with natural cut off point’s 39.18 > 30, meaning that students’ perceptions of using Nearpod show positive perceptions. It is due to the contents or features on Nearpod are more challenging for students and more inspiring for students to learn online, this Nearpod apps is helpful for teachers when delivering material and conducting direct assessments, as well as for students when getting teaching materials. In addition, in the Nearpod apps provides other facilities such as the Nearpod VR apps which allows teachers to take students virtually anywhere in the world without additional hardware